2020
DOI: 10.3310/phr08060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco tax increases and industry pricing on smoking behaviours and inequalities: a mixed-methods study

Abstract: Background Increasing tobacco prices through taxation is very effective for reducing smoking prevalence and inequalities. For optimum effect, understanding how the tobacco industry and smokers respond is essential. Tobacco taxation changes occurred in the UK over the study period, including annual increases, a shift in structure from ad valorem to specific taxation and relatively higher increases on roll-your-own tobacco than on factory-made cigarettes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 103 publications
(145 reference statements)
0
24
0
Order By: Relevance
“…Tax increases reduce smoking and increase quit attempts at the population level [27,28], but research seeking to assess their effects on established smokers has identified inconsistent effects [29][30][31][32]. Popular media reports on tax increases typically assume that established smokers will not quit and instead will switch to discount brands and seek out lower-taxed or illicit tobacco [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Tax increases reduce smoking and increase quit attempts at the population level [27,28], but research seeking to assess their effects on established smokers has identified inconsistent effects [29][30][31][32]. Popular media reports on tax increases typically assume that established smokers will not quit and instead will switch to discount brands and seek out lower-taxed or illicit tobacco [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] However, tobacco companies can shift tax increases across brand portfolios to preserve affordability for price-sensitive consumers; for instance, charging extra for more expensive variants (overshifting) and absorbing tax increases for the least expensive variants (undershifting). [22][23][24][25][26] Consequently, there is growing interest in non-taxation mechanisms for price control, including a minimum mark-up on wholesale price, a price cap to limit overshifting duty increases onto premium products and a minimum retail price (hereafter 'minimum pricing'). 27 28 Sales modelling data suggest that minimum pricing may reduce smoking prevalence, and the effects may be greater than achieved through taxation alone.…”
Section: Introductionmentioning
confidence: 99%
“…13 In other countries such as the UK, tobacco companies have engaged in strategies apparently designed to minimise the impact of tax increases by gradually passing them on to consumers. [13][14][15] By adding a small proportion of the price increase over several months before and/or after the tax increase, rather than all at once on the date on which the tax increase comes into effect, they 'cushion' the effect of the tax increase on the consumer.…”
Section: Introductionmentioning
confidence: 99%